Monitoring of loads and recovery perceived during weeks with different schedule in young soccer players - Gjaka, M.; Tschan, H.; Francioni, F. M.; Tishkuaj, F.; Tessitore, A. (Kinesiologia Slovenica, 2016)
In soccer, to prescribe tailored training and recovery programs requires coaches to be aware of how both internal and external training loads affect individual players` perfor-mances. This study aimed to collect players` session rating of perceived exertion (RPE) responses, recovery scores, and training log during four weeks planned with two conditions [one match (W1match) and two matches (W2 match)] to investigate differences, if any, between the conditions and play roles. Twenty two players from a youth team of a Kosovan elite soccer club (age: 14.5 ± 0.3 yrs, height: 174 ± 7.9 cm, body mass: 60.1 ± 7.9 kg) participated in this study. Individual session-RPE and recovery data were collected by means of an Albanian version of the RPE Borg`s CR10 and a modified total quality recovery (TQR) scale. The weekly match conditions showed significantly (p The Albanian version of Borg`s CR10 scale showed to be a useful tool to depict players` ITLs and recovery status during (W1match and W2 match) conditions. Consequently, their use can be suggested to Albanian speaking youth soccer coaches.